Analisis Mitigasi Bencana Abrasi Pada Kawasan Pesisir Kecamatan Galesong Kabupaten Takalar - Syahrul Syahrul; Agus Salim; Rusneni Ruslan (Fakultas Teknik Universitas Bosowa, 2020)
The purpose of this study is to identify what factors cause abrasion in the coastal area of Galesong District and to formulate directions for abrasion disaster mitigation in the coastal area of Galesong District. Based on the results of the analysis, there are several factors that influence the occurence of abrasion at the Boddia Village study site, including the unavailablity of veggetation on the coast, the flat slope factor, the soil type factor that has a mud or clay structure, geological factors that are easily eroded by sea waves, factors of sandy beach types and no coral reefs,tidal factors of sea water that can produce wafes, and factors of sand mining activities that have changed the conditions of sea depth in the study locations. And the froms of mitigations efforts that can be done are in the form of making revetments (coastal cliff protectors), making breakwaters (talud) and prohibiting coastal sandsmining activities.